Red Dwarf. III [videorecording (DVD)] - Grant, Rob (Robert Ray); Naylor, Doug; Bye, Ed; Barrie, Chris, 1960-; Charles, Craig, 1964-; John-Jules, Danny; Llewellyn, Robert, 1956-; Hayridge, Hattie (Warner Home Video, 2004)
The inept crew stumble further into deep space facing an emotion-sucking polymorph, a psychotic mechanoid and a version of Earth where time runs backwards.